The Impact of EU Accession on Regional Business Cycle Synchronisation and Sector Specialisation - Jürgen Bierbaumer-Polly; Peter Huber; Petr Rozmahel (Austrian Institute of Economic Research (WIFO), 2015)
According to difference-in-difference estimates business cycle synchronisation and similarity in sector structures between acceding and pre-existing regions reduced after Eastern Enlargement. Results for Northern enlargement are more ambiguous. In both enlargements, however, region pairs affected by enlargement with highly synchronised business cycles before enlargement experienced smaller increases in business cycle synchronisation and weaker reductions of structural differences relative to similar unaffected region pairs than region pairs with less synchronised business cycles. Similarly, affected regions that were more similar in terms of sector structure before enlargement experienced larger reductions in structural differences and business cycle synchronisation than similar unaffected region pairs.
Keywords: 330; business cycle correlation; sector specialisation; EU enlargement; difference-in-difference